Die lewe en werk van Karl Barth (1886–1968): ŉ Leksikografiese bydrae tot Reformasie 500 - Wyk, Gabriël M. J.van (HTS teologiese studies, 2017)
Karl Barth was a leading thinker within an influential theological direction that arose in Europeafter the First World War, known as dialectical theology. Comprehensive introductions to thelife and work of Barth in the South African theological journals, written in Afrikaans, eitherdoes not exist, or are difficult to trace for the Afrikaans readership. This article on Barth aims tofill the gap by offering a lexicographical contribution on the life and work of Barth. The focus ofthis article is on Barth as a Reformed theologian. The theme of the New Testament and systematictheology is essentially the same, namely to explain the concept of Christian self-understandingas an eschatological event in which faith is expressed for the sake of faith in God and only inGod. Barth explained the same theological concepts with his theology as those that wereexplained by the church reformers of the 16th century, but under radically new circumstances.The so-called modern and postmodern people of our time not only broke ties with the past, butin the process they also lost their ability for using historical-critical patterns of thought that triesto bridge historical distances, and therefore, sacrificed all efforts to think systematically on thealtar of relativism. We can learn from Barth what systematic reformed theology really is.